THE DEVELOPMENT OF AL-QIRᾹ’ᾹT AL-SAB' LEARNING METHOD BY QᾹRI’S IN LANGSA CITY - fauziah, cut; Wahid, Fatin Nabilah (Jurnal At-Tibyan: Jurnal Ilmu Alqur'an dan Tafsir, 2021)
The development of al-qirā’āt al-sab' is an activity that is necessarily conducted by every qirā’ah teacher (qāri'). It is essential to transfer the correct readings according to the provisions recommended in Islamic law. Therefore the development of al-qirā’āt al-sab' must be encouraged in the Langsa City community. The purpose of this study was to see the qirā'ah (qāri') teachers in developing the al-qirā'āt al-sab' learning method in Langsa City. By conducting interviews with qirā'āt teachers in Langsa City and using qualitative data analysis, it shows that the qāri's develop al-qirā’āt al-sab' by holding al-qirā’āt al-sab' learning in their respective homes. The methods used are bi al-ifrād, Jibrīl, Talaqqī, and bi al-jamā' with practical learning models. The community's positive responses to al-qirā’āt al-sab' learning activities help them to learn al-qirā’āt al-sab,' while the negative ones are they felt prestige or embarrassed and thought it was unimportant to participate in this activity.